Strangles in a stallion in southeast Nigeria: clinical and pathological report - Okolo, CC; Igwe, AO; Ugochukwu, IC; Omeke, JN; Anyogu, DC; Ogbuanya, KO; Nweze, NE; Shoyinka, SVO (Journal of the Hellenic Veterinary Medical Society, 2023)
ABSTRACT. Streptococcus equi subspecies equi is the causative agent of strangles, a highly contagious mucopurulent upper respiratory tract infection of horses. This report describes the clinicopathologic findings of a fatal case of pulmonary form of strangles in a two-and-half-year-old stallion presented at a Veterinary Teaching Hospital in Southeast Nigeria. Treatment was attempted in quarantine using high doses of procaine penicillin; but it was unsuccessful. The clinical signs observed in the affected horse include a left unilateral supra-orbital swelling containing purulent matter, which progressed to a chronic intractable exudative pus. Anaemia with leukocytosis (due to neutrophilia) were observed in the haematologic parameters. Gross and histologic lesions were multifocally extensive abscessing necrotic lymphadenitis and bronchopneumonia with inflammatory oedema and infiltrate of polymorphonuclear leukocytes.